Maternal predictive factors for fetal congenital heart block in pregnant mothers positive for anti-SS-A antibodies. Issue 4 (3rd July 2016) - Tsuboi, Hiroto; Sumida, Takayuki; Noma, Hisashi; Yamagishi, Kazumasa; Anami, Ai; Fukushima, Kotaro; Horigome, Hitoshi; Maeno, Yasuki; Kishimoto, Mitsumasa; Takasaki, Yoshinari; Nakayama, Masahiro; Waguri, Masako; et al.
Abstract: Objective : To determine the maternal predictive factors for fetal congenital heart block (CHB) in pregnancy in mothers positive for anti-SS-A antibodies. Methods : The Research Team for Surveillance of Autoantibody-Exposed Fetuses and Treatment of Neonatal Lupus Erythematosus, the Research Program of the Japan Ministry of Health, Labor and Welfare, performed a national survey on pregnancy of mothers positive for anti-SS-A antibodies. We analyzed 635 pregnant mothers who tested positive for anti-SS-A antibodies before conception but had no previous history of fetal CHB. We performed univariate and multivariate analysis (models 1, 2, and 3 using different set of independent variables) investigated the relation between risk of fetal CHB and maternal clinical features. Results : Of the 635 pregnant mothers, fetal CHB was detected in 16. Univariate analysis showed that fetal CHB associated with use of corticosteroids before conception (OR 3.72, p  = 0.04), and negatively with use of corticosteroids (equivalent doses of prednisolone (PSL), at ≥10 mg/day) after conception before 16-week gestation (OR 0.17, p  = 0.03). In multivariate analysis, model 1 identified the use of corticosteroids before conception (OR 4.28, p  = 0.04) and high titer of anti-SS-A antibodies (OR 3.58, p  = 0.02) as independent and significant risk factors, and model 3 identified use of corticosteroids (equivalent doses of PSL, at ≥10 mg/day) after conception before 16-week gestation as independent protective factor against the development of fetal CHB (OR 0.16, p  = 0.03). Other maternal clinical features did not influence the development of fetal CHB. Conclusion : The results identified high titers of anti-SS-A antibodies and use of corticosteroids before conception as independent risk factors, and use of corticosteroids (equivalent doses of PSL, at ≥10 mg/day) after conception before 16-week gestation as an independent protective factor for fetal CHB.